La relación entre la inteligencia emocional y el síndrome de burnout en profesores de educación básica - Bernal Paz, Romina Vanessa del Carmen (2024)
The educational system was one of the areas that underwent the greatest changes during the COVID-19 pandemic, causing both teachers and students to adapt to new teaching-learning methods, and resulting in high levels of stress in educators, who face these situations using socio-emotional skills, such as emotional intelligence, to cope with job demands. Therefore, the present study aims to determine the relationship between burnout and emotional intelligence in school-level teachers during the COVID-19 pandemic period; through an analysis of quantitative studies that were published in the years from 2021 to 2024. The PRISMA guide is used to conduct the methodology of this study, our research was carried out in the Scopus and Web of Science databases. 216 studies were identified; and considering inclusion and exclusion criteria, 10 quantitative investigations were selected. The results demonstrate the existence of a negative and significant correlation between both variables. In most cases, emotional intelligence plays a protective role against burnout.